Memperjelas Variasi Bahasa Melalui Faktor Sosial dalam Percakapan Pemeran Tokoh di Media Webseries “Imperfect The Series S2 Episode 1-5”: Perspektif Sosiolinguistik - Bhrata, Pramudya Dhana; Yustanto, Henry; Yulianti, Wiwik (Universitas Batanghari Jambi, 2024)
This paper aims to describe research information regarding language variations through socialfactors in the conversations of characters in the media webseries